2007
DOI: 10.1016/j.ydbio.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

even-skipped has gap-like, pair-rule-like, and segmental functions in the cricket Gryllus bimaculatus, a basal, intermediate germ insect (Orthoptera)

Abstract: Developmental mechanisms of segmentation appear to be varied among insects in spite of their conserved body plan. Although the expression patterns of the segment polarity genes in all insects examined imply well conserved function of this class of genes, expression patterns and function of the pair-rule genes tend to exhibit diversity. To gain further insights into the evolution of the segmentation process and the role of pair-rule genes, we have examined expression and function of an ortholog of the Drosophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 32 publications
5
54
0
Order By: Relevance
“…The Tribolium mlpt gene does not code for a transcription factor but for a polycistronic mRNA that encodes several peptides. Also the analysis of the eve gene uncovered a gap function for eve in both Oncopeltus and Gryllus (Liu and Kaufman, 2005a;Mito et al, 2007). This data suggest some gap genes might have lost their gap function during the transition to Drosophila long germ segmentation.…”
Section: Divergent Upstream Mechanisms I: Gap Genesmentioning
confidence: 84%
See 2 more Smart Citations
“…The Tribolium mlpt gene does not code for a transcription factor but for a polycistronic mRNA that encodes several peptides. Also the analysis of the eve gene uncovered a gap function for eve in both Oncopeltus and Gryllus (Liu and Kaufman, 2005a;Mito et al, 2007). This data suggest some gap genes might have lost their gap function during the transition to Drosophila long germ segmentation.…”
Section: Divergent Upstream Mechanisms I: Gap Genesmentioning
confidence: 84%
“…RNA interference (RNAi) experiments in Gryllus showed that eve acts as a canonical pair rule gene but only in the anterior segments (Mito et al, 2007). eve in Gryllus and Oncopeltus in addition seems to have a gap function (Liu and Kaufman, 2005a;Mito et al, 2007), which will be discussed below. In insects, pair rule gene orthologs thus seem to act as in a double segmental periodicity and thus as canonical pair rule genes.…”
Section: The Transition From a Non-periodic To A Periodic Pattern: Ormentioning
confidence: 94%
See 1 more Smart Citation
“…Firstly, there is evidence that hunchback (hb) and Distal-less (Dll) perform gap gene-like functions during formation of the prosomal segments of spiders Pechmann et al, 2011). Secondly, the orthologues of Drosophila pair-rule genes are also expressed in the SAZ and segments of short-germ arthropod embryos, which is consistent with roles in segmentation in these animals, although it is likely that these genes were expressed in single rather than double segmental periodicity ancestrally in arthropods (Frasch et al, 1987;Sommer and Tautz, 1993;Patel et al, 1994;Damen et al, 2000Damen et al, , 2005Davis et al, 2001;Dearden et al, 2002;Chipman et al, 2004b;Schoppmeier and Damen, 2005b;Choe et al, 2006;Damen, 2007;Mito et al, 2007;Chipman and Akam, 2008;Janssen et al, 2011;Sarrazin et al, 2012;Brena and Akam, 2013;Green and Akam, 2013). Finally, the expression and function of segment polarity genes are highly similar across arthropods (Damen, 2002;Hughes and Kaufman, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…Posterior segment addition with a single-segmental periodicity likely represents the ancestral mechanism, as suggested by morphological observations and gene expression analysis Damen 2005, Janssen 2011). Evidence for double-segmental patterning mechanisms in the blastoderm, superficially comparable to Drosophila pair-rule patterning, has, however, been found in distantly related arthropods (Dearden et al, 2002, Janssen et al, 2012 Double-segmental patterning has also been found in tissue that is generated from the posterior segment addition zone in the beetle Tribolium castaneum (Choe et al, 2006) in addition to other insects (Davis et al, 2001, Mito et al, 2007, Erezyilmaz et al, 2009) and a distantly related arthropod, the centipede Strigamia maritima (Chipman et al, 2004). These findings support the idea that a double-segmental posterior patterning system may be a conserved component of arthropod (or at least mandibulate) segmentation.…”
mentioning
confidence: 99%